When The Bus Hits The Road: The Lived Experiences of School Bus Stewards in Dealing with Student Passengers - Maidie P. Acosta, RL, MAIE-AS,; Leandro Dominic F. Luceño II,; Rovic Vincent R. Delos Reyes,; Deyniel Ver G. Silvederio,; Gian Carlos D. Espenilla,; Isaiah David V. Gapas,; Xymon Benedict R. Balbin, (Eximia, 2024)
Introduction/Methodology: School bus stewards providing student passengers with a secure means of transportation from home to school is essential to fostering a supportive learning environment. School bus stewards play a vital role in guaranteeing the security and welfare of pupils on their daily commute. This research employed a qualitative approach, specifically a phenomenological research design, to delve into the experiences of the school bus stewards. Result: The three themes that can be found are: Behavioral Support, Management Effort, and Emotional Comfort. With three sub themes under each theme; School bus stewards utilize strategies to address and mitigate disruptive behaviors among student passengers, They also effectively manage student passenger behavior, ensuring a safe and orderly transportation environment while showcasing to the resilience of school bus stewards amidst challenges posed by disruptive behaviors of student passengers. Discussion: School bus stewards highlighted proactive approaches like open communication to reinforce positive student passenger behavior, along with clear rules and consequences. Collaborating with parents fosters a connected bus environment. School bus stewards use problem-solving, distractions, and positive relationships to manage disruptions effectively. They prioritize emotional comfort by resolving conflicts, promoting relaxation, and addressing environmental stressors, creating a positive transportation atmosphere. Conclusion: School bus stewards prioritize supporting, and comforting to manage student passenger behavior, advocating for ongoing program improvement and further research to enhance safety and transportation experiences.